2021
DOI: 10.3390/foods10102242
|View full text |Cite
|
Sign up to set email alerts
|

Tebuconazole Fungicide Induces Lipid Accumulation and Oxidative Stress in HepG2 Cells

Abstract: Tebuconazole (TEB), a triazole fungicide, is frequently applied to agriculture for the increase of food production. Although TEB causes liver toxicity, its effects on cellular lipid accumulation are rarely investigated. Therefore, this study aimed to study the effects of TEB on lipid metabolism and accumulation in HepG2 cells. HepG2 cells were exposed to 0–320 µM TEB for 1–24 h. TEB (20–80 µM, 24 h)-treated cells showed lipid accumulation. Further, TEB (20–80 µM, 1–12 h) increased the nuclear translocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…Several studies have demonstrated that cell death is induced via various pathways following TEB exposure. In some studies, TEB induced ROS-mediated cell death via mitochondrial dysfunction in human colon carcinoma, cardiac, and hepatic cells [13,34,35]. In other studies, TEB induced apoptosis via ROS in the kidney and liver [36,37], similar to previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated that cell death is induced via various pathways following TEB exposure. In some studies, TEB induced ROS-mediated cell death via mitochondrial dysfunction in human colon carcinoma, cardiac, and hepatic cells [13,34,35]. In other studies, TEB induced apoptosis via ROS in the kidney and liver [36,37], similar to previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…Hepatotoxicity is also observed with signs of hepatocyte dystrophy [4]. In addition, studies of tebuconazole accumulation in HepG2 cells and associated lipid metabolic disorders led to suggestion that human exposure to tebuconazole may be a risk factor for the development of nonalcoholic fatty liver disease [5].…”
mentioning
confidence: 99%